Beyond Engagement: Rethinking Media Effects in an Era of Infinite Feeds - Handoko, Handoko (Journal of Digital Sociohumanities, 2025)
Infinite feeds have conditioned us to think of engagement metrics — such as clicks, views, and watch time — as a shorthand for media efficacy. But participation is a behavioral proxy, not a societal endpoint. This editorial review reframes a media effects research agenda in terms more suitable for exposure–experience–effect and further proposes a pragmatic approach that incorporates equity and public value, in addition to impact. (1) situate engagement in historical and recent effects lines of thinking, (2) diagnose methodological and ethical limitations to a focus on one’s audience as a measurable object, (3) offer an alternative triad of measurement–mechanism–meaningful change and a four-family schema for outcomes including informational quality, personal well-being, civic capacity, and cultural agency; (4) provide mixed-methods designs along with subgroup approaches for causal inference and distributional harms; and (5) translate the rethinking into checklists for authors, reviewers, and designers. We contend that the role of media-effects research is to inform us about what changes, for whom, and at what cost, not just how long attention can be held. The article concludes with standards and statements that can be adopted directly into editorials.